2009
DOI: 10.1093/carcin/bgp152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folic acid supplementation on the progression of colorectal aberrant crypt foci

Abstract: Whether or not folic acid supplementation promotes the progression of colorectal preneoplastic lesions to cancer is an important public health issue, given mandatory fortification and widespread supplemental use of folic acid in North America. We investigated the effect of folic acid supplementation on the progression of aberrant crypt foci (ACF), the earliest precursor of colorectal cancer. Male Sprague-Dawley rats (n = 152) were placed on a control diet (2 mg folic acid/kg diet) at weaning and ACF were induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 49 publications
1
52
0
1
Order By: Relevance
“…lesions, similar to the tumor promoting effect of folic acid supplementation on established (pre)neoplastic colonic lesions (11)(12)(13)(14). Another potential explanation for the contradictory finding between these studies is that terminal end bud density at puberty may not be a consistent predictor of mammary tumor risk in rodents as suggested by recent studies (40,41).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…lesions, similar to the tumor promoting effect of folic acid supplementation on established (pre)neoplastic colonic lesions (11)(12)(13)(14). Another potential explanation for the contradictory finding between these studies is that terminal end bud density at puberty may not be a consistent predictor of mammary tumor risk in rodents as suggested by recent studies (40,41).…”
Section: Discussionmentioning
confidence: 69%
“…Amino acid-defined diets containing different levels of folic acid constitute a standard method of providing supplemental dietary folate in rodents and have been extensively used in previous studies of dietary folate and cancer in rodents (10)(11)(12)(13)(14) including mammary tumors (25,26). The control diet containing 2 mg of folic acid/kg diet is the basal dietary requirement (BDR) for rats (27) and was selected to represent the recommended dietary allowance for humans (0.4 mg/d of dietary folate equivalents).…”
Section: Dams Pupsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies thus far have been inconsistent and not confirmed this assumption save for a possible benefit in stroke prevention (Chen, J (J), Xu, X (X), et al, 2010;Wang et al, 2007;Robinson et al, 1998) and thrombophilia. Alarmingly, there are now laboratory animal (Lindzon et al, 2009;Ly et al, 2011) and epidemiological reports pointing to excessive malignancy, including prostate (Figueiredo et al, 2009), breast ({Campbell 2002Chen et al, 2005;Ericson et al, 2009;Stevens et al, 2010) colorectal and other cancers (Kim, 2005) associated with both hyper and hypo-sufficiency of folate and folate enzyme polymorphisms, reviewed by Young-In Kim and others Kim, 2008;Kim, 2005;Smith et al, 2008) …”
Section: Folate Fortification Some Adverse Effectsmentioning
confidence: 99%
“…In addition, polyglutamyl folate shows bioavailability equal to or higher than that of monoglutamyl folate (10)(11)(12). Pteroylmonoglutamyl folate has shown some adverse effects on human health (13,14). Therefore, many countries in EU ban the fortification of food with pteroylmonoglutamyl folate and recommend that people consume food with high native folate.…”
mentioning
confidence: 99%